Anti-Inflammatory Activity Of Hydroalcoholic Extract Of Phyllanthus Amarus Leaves Against Raw264.7 Cell Line - Ishwarya S; Dr. Parameshwari; Dr. Geetha R.V (Journal for ReAttach Therapy and Developmental Diversities, 2023)
INTRODUCTION The inflammatory response is a basic physiological reaction of the immune system to tissue damage, infection, and any other pathological processes. Acute inflammation has a significant contribution during body protection and healing; however, chronic or long-term inflammation can result in multiple diseases that include heart diseases, auto-immune diseases, and cancer. Hence, finding natural compounds with strong anti-inflammatory effects has gradually become an important issue of medical science. Phyllanthus amarus can be referred to as “Chanca piedra” or “Stonebreaker”. It can be found in many parts of the body. It is an old remedy for many illnesses such as jaundice, renal calculus, or infections. Recently, various scientific studies have investigated the healing potentials in Phyllanthus amarus, especially for fighting inflammation. AIM AND OBJECTIVE To evaluate the anti - inflammatory activity of hydroalcoholic extract of phyllanthus amarus leaves against RAW264.7 cell line CONCLUSION The findings of this study support the traditional use of Phyllanthus amarus as an anti-inflammatory agent in traditional medicine systems.The hydroalcoholic extract of Phyllanthus amarus leaves demonstrates significant anti-inflammatory activity against the RAW264.7 cell line. This is evidenced by the reduction in the levels of pro-inflammatory mediators such as cytokines (TNF-a, IL-1ß, IL-6) and nitric oxide (NO) compared to control groups